Acidogenic fermentation for the production of volatile fatty acids from cassava sour starch extraction process wastewater (2025)
Cassava and its processed products, such as sour starch, form the economic backbone of various communities in Colombia. However, their production generates effluents with high organic loads, cyanide concentrations, and acidic pH levels, leading to significant deterioration of receiving wáter sources. If these discharges are not properly treated beforehand, bodies of water may become unsuitable for human consumption, fishing, or recreation. Previous research indicates that this type of wastewater can be treated through anaerobic digestion, yielding methane as the primary product. However, studies also suggest that the volatile fatty acids produced during the acidogenic phase of anaerobic digestion, known as acidogenic fermentation, have valuable applications in various chemical and biological processes. This doctoral thesis begins with an introduction to the environmental issues caused by effluents from sour starch extraction from cassava, along with an analysis of previous research and emerging trends in its treatment. It also outlines the challenges that motivated this study and led to the establishment of three specific objectives (Chapter 1). Next, acidogenic fermentation and volatile fatty acid production are examined as alternatives for wastewater treatment through a bibliometric análisis of existing scientific literature (Chapter 2). This analysis identified key operational variables, which were evaluated at the laboratory scale for the substrate of interest. The individual and interactive effects of fermentation time and pH (Chapter 3), as well as the substrate-microorganism relationship and temperature (Chapter 4), were examined. Additionally, recognizing the importance of modeling in complementing experimental trials and enhancing the understanding of biological processes, a kinetic study was conducted on the acidogenic fermentation of wastewater from cassava processing. This study identified the models that best fit soluble organic matter consumption and volatile fatty acid production (Chapter 5). Finally, this thesis synthesizes the results and outlines perspectives for future research in the field (Chapter 6).